Super-resolution imaging of remodeled synaptic actin reveals different synergies between NK cell receptors and integrins. - Brown, A; Dobbie, I; Alakoskela, J; Davis, I; Davis, D (2012)
Natural killer (NK) cells secrete lytic granules to directly kill virus-infected or transformed cells and secrete cytokines to communicate with other cells. Three-dimensional super-resolved images of F-actin, lytic granules, and IFN-γ in primary human NK cells stimulated through different activating receptors reveal that both IFN-γ and lytic granules accumulated in domains where the periodicity of the cortical actin mesh at the synapse opened up to be penetrable. Ligation of some activating receptors alone (eg, CD16 or NKG2D) was sufficient to increase the periodicity of the actin mesh, but surprisingly, ligation of others (eg, NKp46 or CD2) was not sufficient to induce cortical actin remodeling unless LFA-1 was coligated. Importantly, influenza virus particles that can be recognized by NK cells similarly did not open the actin mesh but could if LFA-1 was coligated. This leads us to propose that immune cells using germline-encoded receptors to directly recognize foreign proteins can use integrin recognition to differentiate between free pathogens and pathogen-infected cells that will both be present in blood. This distinction would not be required for NK cell receptors, such as NKG2D, which recognize host cell-encoded proteins that can only be found on diseased cells and not pathogens.